2010
DOI: 10.1353/foc.0.0043
|View full text |Cite
|
Sign up to set email alerts
|

Civic Engagement and the Transition to Adulthood

Abstract: Constance Flanagan and Peter Levine survey research on civic engagement among U.S. adolescents and young adults. Civic engagement, they say, is important both for the functioning of democracies and for the growth and maturation it encourages in young adults, but opportunities for civic engagement are not evenly distributed by social class or race and ethnicity. Today's young adults, note the authors, are less likely than those in earlier generations to exhibit many important characteristics of citizenship, rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
159
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 479 publications
(164 citation statements)
references
References 31 publications
3
159
0
2
Order By: Relevance
“…In addition to these external influences on civic engagement, schools themselves have also been identified as important sites promoting civic engagement. TorneyPurta et al (2001), Flanagan, Martínez, Cumsille, and Ngomane (2011), Youniss (2011 and Flanagan and Levine (2010) found that students' engagement in extracurricular activities in high school and their feelings of social connectedness to community institutions predicted voting and other forms of civic engagement in young adults. Jahromi, Crocetti, and Buchanan (2012), in cross-national studies, compared community-oriented and political civic engagement activities and intentions among adolescents in Italy and the US.…”
mentioning
confidence: 99%
“…In addition to these external influences on civic engagement, schools themselves have also been identified as important sites promoting civic engagement. TorneyPurta et al (2001), Flanagan, Martínez, Cumsille, and Ngomane (2011), Youniss (2011 and Flanagan and Levine (2010) found that students' engagement in extracurricular activities in high school and their feelings of social connectedness to community institutions predicted voting and other forms of civic engagement in young adults. Jahromi, Crocetti, and Buchanan (2012), in cross-national studies, compared community-oriented and political civic engagement activities and intentions among adolescents in Italy and the US.…”
mentioning
confidence: 99%
“…As students have expressed a desire to perform more community work and become more engaged in social justice activities both on and off campus, institutes of higher education have begun working to fulfill that desire, offering an increasing number of service learning courses, civic engagement minors and majors, and co-curricular service and civic engagement activities Colby, Ehrlich, Beaumont, & Stephens, 2003;Steinberg, Hatcher, & Bringle, 2011). As these programs grow and expand, there is a strong desire by social work and other allied fields to support students as they transition out of the college/university environment and adapt to the various ways that social justice activism takes shape in their lives (Flanagan & Levine, 2010;Wendlandt & Rochlen, 2008).…”
Section: Background Literaturementioning
confidence: 99%
“…Traditional civic practices such as union membership, newspaper readership, interactions with political parties and engagement in community projects, have seen a marked decline in the United States over the last few decades (Delli Carpini, 2000;Flanagan & Levine, 2010;Putnam, 2001). Similar trends have been seen in Europe, where youth are found to turn away from traditional political parties and rather engage in project-oriented protest movements (Sloam, 2014).…”
Section: Civic Organisations and Youthmentioning
confidence: 99%
“…However, youth practices of civic engagement are changing from long-term engagement with formal civic organisations -such as political party membership, membership in humanitarian organisations and subscription to newspapers -to short-term engagement in project-based initiatives, such as protest movements and online campaigns on social media (Flanagan & Levine, 2010). While social media are seen as a promising arena for civic organisations to facilitate youth civic engagement (Brandtzaeg, Haugstveit, Lüders, & Følstad, 2015;de Zuniga, 2015;Wells, 2014), civic organisations are struggling to adapt to the changing networked media and civic cultures of young people Delli Carpini, 2000;Loader, Vromen, & Xenos, 2014).…”
Section: Introductionmentioning
confidence: 99%